Interracial relationships in Singapore : is love colourblind? - Lee, Janice Sijie. (2013)
This paper examined interracial relationships amongst young adults in Singapore and if their openness to interracial relations were due to their upbringing and social circles or if they had differing values and attitudes from the people around them. Qualitative interviews were conducted amongst ten individuals in interracial relationships. The results found that the individuals hold a unique position in society as they are caught between being open and accepting of a different race and culture and respecting their parent’s more traditional and conservative opinions towards racial relationships. Overall, we recognise that the demographics of interracial couples today are different from what is often portrayed in the available literature and media but at the same time they still face numerous challenges in gaining acceptance towards their relationship.